Staking a Claim in Paradise : The Appropriation of Central Asia by the Capitals of China (1625-1945) - Forêt, Philippe (My University, 2010)
Lecture given at the China in Asia colloquia series, 2010-2011 OBJECTIVE Understand the non-Chinese notions at work in landscape-making and in thegarden architecture of the imperial capitals of China. METHODOLOGY Examine imperial villas, gardens and temples. Hypothesis: These sites represent physically and explicitly theories andtechniques on landscape appropriation. Case study: The residences of the Qing dynasty (1625-1912) in Shenyang, Beijing (Yuanming yuan and Yihe yuan) and in Chengde (Bishu shanzhuang),and those of Manchoukouo (1932-1945). EXPECTED RESULTS Conceptualize the Qing landscape through changes in scale rather thanthrough ruptures in time.
Keywords: historical geography; Central Asia and China; imperial landscape; cultural landscape; notion and representation; place and scale; state building; Qing dynasty (1644-1912) and successor states; capital cities; frontier studies; Beijing; Chengde; Shenyang; Changchun; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::History of religion